Pressure-flow studies in man. An evaluation of the duration of the phases of systole - Harley, Alexander; Starmer, C. Frank; Greenfield, Joseph C., Jr. (The Journal of Clinical Investigation, 1969)
This study was designed to assess the independent effects of stroke volume and heart rate on the phases of systole and other selected hemodynamic parameters. By means of the pressure gradient technique instantaneous blood pressure and flow were recorded in the ascending aorta at fixed ventricular rates in five patients with complete heart block and in four patients with atrio-ventricular dissociation induced by ventricular pacing. Because of the variable contribution of atrial systole to ventricular filling, a wide range of stroke volumes were observed at each heart rate. The results indicate that the duration of ejection bears a close direct linear relationship to stroke volume while heart rate has only a weak but independent relation. On the other hand, the duration of total systole is related chiefly to the heart rate but stroke volume exerts an important independent effect. In a given patient, both duration of ejection and pulse pressure reflect changes of stroke volume and the product of the duration of ejection and the pulse pressure shows a good correlation with the stroke volume.